2018
DOI: 10.1111/jphs.12268
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems and health-related quality of life in outpatients with type 2 diabetes: a cross-sectional study from Jordan

Abstract: Objectives This study aimed to assess the different types of drug-related problems (DRPs) among diabetic patients and to study the effect of those DRPs on health-related quality of life (HRQoL) of this population. Methods The current retrospective cross-sectional study was conducted at outpatients' clinics at the Jordan University Hospital. During the study period, a total of 91 patients with type 2 diabetes were recruited. Patients' medical information was used to assess the different DRPs and to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(60 reference statements)
2
5
0
Order By: Relevance
“…Drug-related problems (86.6 %) and nonadherence (70.1 %) were prevalent in the current study (2.1 DRP per patient). Being a T2DM patient was associated with a higher chance of having multiple DRPs, similar to previous findings reported in Jordan [20]. Over 190 different DRPs were identified in the current study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Drug-related problems (86.6 %) and nonadherence (70.1 %) were prevalent in the current study (2.1 DRP per patient). Being a T2DM patient was associated with a higher chance of having multiple DRPs, similar to previous findings reported in Jordan [20]. Over 190 different DRPs were identified in the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Other factors associated with worse QoL and lower EQ-5D scores include female gender, unemployment status, and belief that medications do more harm than good". Other researchers reported that medication-related risk factors, female gender, two classes of DRPs, needing additional drug therapy, wrong drugs, and illiteracy were all associated with worse QoL and lower EQ-5D scores, which is comparable to the findings in this study [17][18][19][20]. It is important to mention the potential factors that may result in variations between studies, such as the fact that they were conducted in different cultural settings, used different tools for the evaluation of HRQoL and DRP, and considered different patientrelated factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…DRP occurs when inappropriate prescribing, ineffective, or unnecessary medication, underdose, overdose, the presence of unwanted drug events, patient non-compliance, and so on [3]. Lack of knowledge and patient noncompliance with medication use can be a significant factor in increasing the risk of DRPs [4]. This study is supported by the results of a study conducted by Al-Azzam in 2016, showing that 82.1% of chronic disease patients need education and counseling [3].…”
Section: Introductionmentioning
confidence: 57%
“…Previous systematic reviews focused on patients with diabetes' admission to hospital due to medication problems 11 , 12 with several reviews focused on patients with type 2 diabetes in an outpatient setting. 13 , 14 While there are various systematic reviews focusing on the identification of DRP in patients with diabetes in a hospital setting, few systematic reviews have been conducted on the prevalence and risk factors in hospitalized patients specifically with type 2 diabetes. Therefore, the aim of this study was to review and assess literature related to DRP in adult hospitalized T2DM patients, focusing on its prevalence and risk factors.…”
Section: Introductionmentioning
confidence: 99%